Blood Money: Incentives for Violence in NHL Hockey - John P. Haisken-DeNew; Matthias Vorell (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2008)
The level of violence in the National Hockey League (NHL) reached its highest point in 1987 and has reduced somewhat since then, although to levels much larger than before the first team expansions in 1967. Using publicly available information from several databases 1996-2007, the incentives for violence in North American ice hockey are analyzed. We examine the role of penalty minutes and more specifically, fighting, during the regular season in determining wages for professional hockey players and team-level success indicators. There are substantial returns paid not only to goal scoring skills but also to fighting ability, helping teams move higher in the playoffs and showing up as positive wage premia for otherwise observed low-skill wing players. These estimated per-fight premia, depending on fight success (10,000 to 18,000), are even higher than those for an additional point made. By introducing a fight fine of twice the maximum potential gain (36,000) and adding this amount to salaries paid for the team salary cap (fines would be 6.7% of the team salary cap or the average wage of 2 players), then all involved would have either little or no incentives to allow fighting to continue.
Keywords: J31; J81; C23; 330; Compensating wage differentials; health risk; violence; subjective indicators; Professioneller Sport; Wintersport; Sportler; Lohnstruktur; Gesundheitsrisiko; Gewalt; USA